Antioxidant enzyme activities of human peripheral blood mononuclear cells exposed to trace elements - Kuppusamy, U.R.; Dharmani, M.; Kanthimathi, M.S.; Indran, M. (2005)
The trace elements copper, zinc, and selenium are important immune modulators and essential cofactors of the antioxidant enzymes. In the present study, the proliferative effect of human peripheral mononuclear cells (PBMCs) that have been exposed to copper, zinc, and selenium and the corresponding activities of antioxidant enzymes, namely superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase, were determined. Zinc and copper stimulated the PBMC proliferation in a dose-dependent manner within the dose range 25-200 Î¼mol/L. SOD and GPx activities in PBMCs exposed to zinc were inhibited, whereas catalase activity was unaffected. All the three antioxidant enzymes in the cells exposed to copper were inhibited. Selenium exerted more potent inhibition of the cell proliferation while causing stimulation of the antioxidant enzymes at the lowest dose (25 Î¼mol/L) than at the highest dose (200 Î¼mol/L) tested. A significant negative correlation was observed between proliferation and antioxidant enzyme (SOD and GPx) activities in traceelement-exposed PBMC. The present findings substantiate the importance of trace elements as immune modulators and the involvement of enzymatic antioxidant system in the immune cell regulation. Â© Copyright 2005 by Humana Press Inc. All rights of any nature, whatsoever, reserved.